Cerebral Hemodynamic Changes After Endovascular Recanalization of Symptomatic Chronic Intracranial Artery Occlusion - Kang, Kaijiang; Yang, Bo; Gong, Xiping; Chen, Xing; Gu, Weibin; Ma, Guofeng; Miao, Zhongrong; Zhao, Xingquan; Ma, Ning (Frontiers in Neurology, 2020)
Objective- We performed this study to evaluate the hemodynamic changes over time after successful endovascular recanalization in patients with symptomatic chronic intracranial artery occlusion (CIAO). Methods and Methods- We included 20 patients with symptomatic CIAO in a high-volume stroke center from June 2014 to June 2019. All subjects were evaluated with CT perfusion (CTP) studies before and after the recanalization. The relative cerebral blood flow (rCBF) in perforating artery territory (PAT) and cortical artery territory (CAT) of occluded arteries were compared before and after the recanalization. The patients were categorized into subgroups based on the time interval from revascularization to post-procedural CTP, occlusion sites and restenosis status. The proportion of rCBF change (rCBFc%) were compared in variable subgroups. Results- The rCBF increased significantly from 0.52 to 0.71 in PAT (P < 0.001) and from 0.59 to 0.85 in CAT (P < 0.001) after recanalization, and there were also statistical differences in variable subgroups except for those with restenosis. The median and interquartile range of rCBFc% were 35.2% (18.6%-56.6%). For patients with short-term follow-up (55.2%), the rCBFc% was relatively higher than that in patients with mid-term (35.4%) and long-term follow-up (32.7%), although without statistical difference (P = 0.273). For patients with restenosis, the rCBFc% was significantly lower than that in patients without restenosis (18.5% versus 37.3%, P = 0.008). Conclusions- In patients with symptomatic CIAO, the CBF may increase and be relatively stable over time after successful recanalization except for restenosis.